Local auxin sources orient the apical-basal axis in Arabidopsis embryos - Robert, Hélène S; Grones, Peter; Stepanova, Anna N; Robles, Linda M; Lokerse, Annemarie S; Alonso, Jose M; Weijers, Dolf; Friml, Jiří (Current biology, 2013)
Establishment of the embryonic axis foreshadows the main body axis of adults both in plants and in animals, but underlying mechanisms are considered distinct. Plants utilize directional, cell-to-cell transport of the growth hormone auxin to generate an asymmetric auxin response that specifies the embryonic apical-basal axis. The auxin flow directionality depends on the polarized subcellular localization of PIN-FORMED (PIN) auxin transporters. It remains unknown which mechanisms and spatial cues guide cell polarization and axis orientation in early embryos. Herein, we provide conceptually novel insights into the formation of embryonic axis in Arabidopsis by identifying a crucial role of localized tryptophan-dependent auxin biosynthesis. Local auxin production at the base of young embryos and the accompanying PIN7-mediated auxin flow toward the proembryo are required for the apical auxin response maximum and the specification of apical embryonic structures. Later in embryogenesis, the precisely timed onset of localized apical auxin biosynthesis mediates PIN1 polarization, basal auxin response maximum, and specification of the root pole. Thus, the tight spatiotemporal control of distinct local auxin sources provides a necessary, non-cell-autonomous trigger for the coordinated cell polarization and subsequent apical-basal axis orientation during embryogenesis and, presumably, also for other polarization events during postembryonic plant life.
Keywords: transport proteinů; proteiny huseníčku; Arabidopsis Proteins; Protein Transport; Seeds; Arabidopsis; Membrane Transport Proteins; rozvržení tělního plánu; membránové transportní proteiny; semena rostlinná; Plant Growth Regulators; regulátory růstu rostlin; Body Patterning; kyseliny indoloctové; Indoleacetic Acids